Answer to ECG Quiz no. 28 - Okreglicki, A. (SA Heart Journal, 2017)
Wide QRS complexes are the result of conduction abnormalities or arise in the ventricles. Conduction abnormalities causing wide QRS may be due to conduction system disorders affecting the bundles, accessory pathways or drugs. Confirmation of bundle branch block requires evidence of rapid conduction of the unaffected bundle. Wide non-conducted QRS complexes are either intrinsic (ventricular escape, accelerated idioventricular rhythm or ventricular tachycardia, as classified by rate) or extrinsic (pacing). Accelerated idioventricular rhythm is usually transient and the result of an acute process: infarction, inflammation or injury (surgery).